2010
DOI: 10.1093/ejechocard/jeq003
|View full text |Cite
|
Sign up to set email alerts
|

The PFO anatomy evaluation as possible tool to stratify the associated risks and the benefits arising from the closure

Abstract: It is possible to suppose that not all PFO have the same prognostic value. The evaluation of two anatomical characteristics can allow to identify those foramina at higher risk and, as a consequence, the patients who could have a major benefit from the closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
5
2
Order By: Relevance
“…Certainly, further studies are necessary to define in symptomatic patients the optimal therapeutic strategy, adapting it to the specific risk profile as not all the PFO could be associated to the same risk of recurrent ischemic events [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, further studies are necessary to define in symptomatic patients the optimal therapeutic strategy, adapting it to the specific risk profile as not all the PFO could be associated to the same risk of recurrent ischemic events [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were classified into three levels: no MBs, negative test for RLS; ≤10 MBs, small or non-significant RLS; >10 MBs or significant RLS. Although there are some cut-off variations, the consensus seems to be that RLS is present if multiple MBs are detected (more than one) and is considered significant whenever more than 10 MBs are detected 21,22,23,24…”
Section: Methodsmentioning
confidence: 99%
“…The results related with the effect of closure of PFO on attacks are controversial. According to the MIST (Migraine Intervention with STARFlex Technology) study, no difference could be found in patients who underwent this procedure in the frequency of migraine attacks 6 months later compared to patients who did not underwent this procedure (34,35).…”
Section: Cardiac Diseasesmentioning
confidence: 99%